Гравет Центральної України та його історичні долі - Залізняк, Л.Л.; Степанчук, В.М.; Вєтров, Д.О.; Товкайло, М.Т.; Озеров, П.І. (Археологія, 2007)
Розглянуто культурно-історичні процеси в пізньому палеоліті Центральної України на матеріалах першої
граветської пам’ятки регіону Троянове-4, що на Кіровоградщині. Особливу увагу приділено проблемі генезису епігравету України. На основании анализа археологических материалов первой в Центральной Украине граветтской стоянки Трояново-4 рассмотрены культурные процессы, имевшие место в регионе в середине позднего палеолита. Авторы
видят аналогии упомянутому комплексу в материалах нижних слоев Владимировки в Побужье, X—VII слоев Молодовы V, граветта Центральной Европы и значительные отличия от комплексов восточного граветта.
Особое внимание уделено возможным путям генезиса эпиграветта Украины, в котором приняли участие как
носители пришлых граветтских традиций, так и местное эпиориньякское население. Based on the analysis of archaeological materials of the first in Central Ukraine Gravettian station Troyanovo 4 the
authors view the cultural processes in the area in the middle of the Upper Paleolithic period. The analogies to the
assemblage mentioned are seen by authors in the materials of the lower layers of Volodymyrivka in the Buh River
Region, of the layers X—VII of Molodove V, and of Central European Gravettian, and the significant distinctions are
seen in Eastern Gravettian assemblages. Spetial attention is payed to the possible routes of genesis of epi-Gravettian
culture in Ukraine. Both incoming barears of Gravettian traditions and local epi-Orignac population took part in
forming the epi-Gravettian culture.